Concrete bridge strengthening and repair - Kennedy Reid, Iain L. (Thomas Telford, 2009)
"Covering a wide range of structural elements and related defects, this collection of twenty concrete bridge strengthening and repair case studies showcases solutions to real problems encountered in the field and the processes by which those solutions were developed. Drawing on a lifetime of experience Atkins consultant Iain Kennedy Reid provides insight into methods of investigation and diagnosis of problems relating to beams, slabs, columns and panel walls, as well as how to apply demand-led research to these problems in a practical way."--Pub. desc.
Includes index.
Keywords: Concrete bridges -- Maintenance and repair.; elektronické knihy; electronic books